Life-threatening hemorrhage from acquired hemophilia A as a presenting manifestation of prostate cancer - Chirag Sheth; Amandeep Gill; Sumeet Sekhon (Greater Baltimore Medical Center, 2016)
Acquired factor VIII deficiency (acquired hemophilia A) is a rare condition characterized by the acquisition of autoantibodies that affect the clotting activity of factor VIII (fVIII). The most common manifestation in affected patients is a hemorrhagic diathesis. This disorder is associated with autoimmune diseases, pregnancy, postpartum period, drugs, and malignancy. Management of this condition begins with attempts to arrest an acute bleed based on the site and severity of bleeding and inhibitor titer. The next priority is eradication of the fVIII antibodies using immunosuppressive therapies. We report the case of a 66-year-old male who presented with spontaneous right thigh hematoma with prolonged activated partial prothrombin time and normal prothrombin time. Mixing studies confirmed the presence of an inhibitor. Further investigation for the underlying etiology of acquired hemophilia A leads to diagnosis of prostate cancer. Treatment consisted of bypassing agents including activated factor VII and activated prothrombin plasma concentrate to arrest the bleeding. Steroids and cyclophosphamide were added to suppress the fVIII inhibitors. Concomitant treatment of locally advanced prostate cancer with chemotherapy confirmed the eradication of the inhibitors. To our knowledge, this is the first reported case of prostate cancer diagnosed and treated simultaneously with acquired hemophilia A resulting in favorable patient outcome.